2020
DOI: 10.1097/j.jcrs.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive intrastromal corneal crosslinking for treatment of low myopia: clinical outcomes using the transepithelial approach with supplemental oxygen

Abstract: Purpose: To evaluate the safety and efficacy of photorefractive intrastromal corneal crosslinking (PiXL) for the treatment of low myopia using the epithelium-on approach with supplemental oxygen. Setting: The Eye Foundation, Coimbatore, India. Design: Prospective interventional case series. Methods: Myopic nonectatic eyes underwent PiXL using the Mosaic system. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 9 publications
9
29
0
Order By: Relevance
“…Supplemental oxygen maintaining a hyperoxic environment in the corneal stroma counteracts oxygen depletion and enhances the reaction further (Hill et al 2019). In the current study, we demonstrated significant improvements in the visual acuity and refraction with stable results up to 24 months, which strengthens previous findings that epi‐on PiXL with high oxygen supply can be used for reduction of low‐grade myopia (Fredriksson et al 2019; El Hout et al 2019; Sachdev et al 2020).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Supplemental oxygen maintaining a hyperoxic environment in the corneal stroma counteracts oxygen depletion and enhances the reaction further (Hill et al 2019). In the current study, we demonstrated significant improvements in the visual acuity and refraction with stable results up to 24 months, which strengthens previous findings that epi‐on PiXL with high oxygen supply can be used for reduction of low‐grade myopia (Fredriksson et al 2019; El Hout et al 2019; Sachdev et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Epi‐on PiXL in high oxygen is a novel therapeutic procedure that reshapes the corneal stroma without the need for epithelial debridement or stromal removal (Lim et al 2017; Fredriksson et al 2019; El Hout et al 2019; Sachdev et al 2020). Epi‐on techniques are beneficial with potentially less postoperative ocular discomfort, faster recovery for the patient and lower risks for serious complications such as postoperative infections and corneal scarring (Meek & Hayes 2013; Stulting et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations